2020
DOI: 10.3390/app10207058
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of a Gear System with Double-Teeth Spalling Fault and Its Fault Feature Analysis

Abstract: Tooth spalling is one of the most destructive surface failure models of the gear faults. Previous studies have mainly concentrated on the spalling damage of a single gear tooth, but the spalling distributed over double teeth, which usually occurs in practical engineering problems, is rarely reported. To remedy this deficiency, this paper constructs a new dynamical model of a gear system with double-teeth spalling fault and validates this model with various experimental tests. The dynamic characteristics of gea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Yang et al [17] established a TVMS model with a gear tooth surface crack and analyzed the effect of the surface crack on the dynamic system. Shi et al [18] investigated the dynamic characteristics of the gear system with a double-teeth spalling fault. They utilized some advanced signal processing methods, including variational mode decomposition, local mean decomposition, and empirical mode decomposition, to successfully extract the fault feature.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [17] established a TVMS model with a gear tooth surface crack and analyzed the effect of the surface crack on the dynamic system. Shi et al [18] investigated the dynamic characteristics of the gear system with a double-teeth spalling fault. They utilized some advanced signal processing methods, including variational mode decomposition, local mean decomposition, and empirical mode decomposition, to successfully extract the fault feature.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [23] demonstrated that tooth spall and sliding friction have an evident effect on kinetic performance. Shi et al [24] discussed the dynamic characteristics of the gear with double-teeth spalling fault. In terms of global dynamics, Ma [25] employed the singularity theory to evaluate the bifurcation characteristics of the gear system with tooth spalling.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [28] demonstrated that tooth spalls and sliding friction have an obvious effect on kinetic performance. Shi et al [29] discussed the dynamic characteristics of a gear with a double-teeth spall fault. Ma [30] employed the singularity theory to evaluate the bifurcation characteristics of a gear system with a tooth spall.…”
Section: Introductionmentioning
confidence: 99%